WORKING CAPITAL DAN LIKUIDITAS: STUDI PADA KOPERASI KOSTRANDA BATAN DI JAKARTA SELATAN - Pattipeilohy, Leonardo Jhones; Yandri, Pitri (Journal of Innovation in Business and Economics, 2016)
The purpose of this study is to analyze the effect of the liquidity on working capital in the Cooperative Kostandra Batan. The measurement standard refers to the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No. 06/Per/M.KUKM /V/2006 on guidelines on the assessment of cooperative achievement. The values tested in this study using regression analysis. The results showed an increase in working capital amounted to 1% will increase the liquidity of 37.3%. Working capital is able to explain the variation of liquidity amounting to 68.9%.